2020
DOI: 10.1080/03019233.2020.1855690
|View full text |Cite
|
Sign up to set email alerts
|

Electrode manufacture for the remelting processes

Abstract: The remelting processes require an electrode which has been made by conventional melting and casting. In this paper, we examine the relation between the electrode manufacturing process and the quality of the remelted ingot which has been made from it. We conclude that the quality of the electrode with respect to segregation, porosity, stress condition and content of non-metallic inclusions is critical to the quality of the remelted ingot. Specific examples of these aspects are presented. It is recommended that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The cracks inflict major defects on the integrity of the VAR process and the final VAR ingot. It is interesting to note that Mitchell has drawn attention to the several shortcomings of electrodes in addition to their bifilm problems [5].…”
Section: The Vim Process and Its Limitationsmentioning
confidence: 99%
“…The cracks inflict major defects on the integrity of the VAR process and the final VAR ingot. It is interesting to note that Mitchell has drawn attention to the several shortcomings of electrodes in addition to their bifilm problems [5].…”
Section: The Vim Process and Its Limitationsmentioning
confidence: 99%
“…At the electrode tip, with the rapid increase in temperature, parts of inclusions decomposed into oxygen and deoxidants, and then removed through slag-steel reactions at the metal-slag interface of the tip, droplet, and steel-pool. [8,9] Noticeably, there were also newly formed inclusions caused by the entrainment of slag and the reoxidation during remelting, [10][11][12] which would reduce the cleanliness of the steel. Burja [13] studied the remelting of the H11 tool steel in the slag composed of CaF 2 , CaO, and Al 2 O 3 as well as very low contents of MgO and SiO 2 and found that the number density and the area fraction of nonmetallic inclusions in the steel decreased and that inclusions of MnS, SiO 2 , and MgO were strongly reduced.…”
Section: Introductionmentioning
confidence: 99%